PELAKSANAAN ULTRASOUND DAN TERAPI LATIHAN PADA KASUS TRINGGER FINGER - Miftahul Jannah; Lisa Agustina; Fauziah Fauziah (Jurnal Real Riset, 2022)
This study aims to determine the effect of ultrasound on reducing pain in the trigger finger and to determine the benefits of exercise therapy with free active exercise and resisted exercise on increasing muscle strength, increasing joint range of motion, increasing activity daily living (ADL) and functional ability of the hand on the trigger finger. This research is a qualitative research with a case study design. The subject of this study is one person, namely the patient who has a disorder. Data were obtained by conducting interviews and performing ultrasound actions. The results showed that after performing physiotherapy intervention with ultrasound modalities and exercise therapy in reducing pain, and increasing the range of motion of the joints 6 times, the results of the assessment of silent pain were T1: 2 to T6: 0, tenderness T1: 5 became T6: 2, motion pain T1: 4 to T6: 2. So it can be concluded that the administration of ultrasound modalities and exercise therapy can reduce pain, and increase the range of motion of the joints. There are several factors that drive the healing, namely: 1. It must be done in good condition so that it can provide a therapeutic effect as expected, 2. High motivation to recover from the patient.Keywords: ultrasound, exercise therapy, trigger finger